2005
DOI: 10.1080/0144619042000287714
|View full text |Cite
|
Sign up to set email alerts
|

Main contractor experiences of partnering relationships on UK construction projects

Abstract: Partnering provides a major opportunity for improving project performance, whilst offering direct benefits to the whole of the supply chain. Many research studies reinforce this assertion although there is less critical analysis examining the nature of partnering in practice and whether the claims made for it are consistently justified. The experiences of commercial surveyors and managers within the UK construction industry have been gathered in a pilot study, drawing on the opinions of 48 commercial managers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 12 publications
4
56
0
1
Order By: Relevance
“…The result also reflects the general industry perception that housebuilding by offsite is more expensive than by traditional construction methods (Birkbeck and Scoones 2005), and supports the finding of a positive correlation between building construction costs and the proportion of openings and prefabricated façade areas of external walls (Stoy et al 2008). Given the typical cost-driven decision philosophy prevailing in the industry (Wood and Ellis 2005), it is understandable that the housebuilders weighed cost criteria most heavily. Some researchers (Blismas et al 2006) have argued against this 'cost myth' and suggested developing rigorous methods for measuring the value of offsite.…”
Section: ; Gibb and Pendlebury 2005; Nao 2007)supporting
confidence: 74%
“…The result also reflects the general industry perception that housebuilding by offsite is more expensive than by traditional construction methods (Birkbeck and Scoones 2005), and supports the finding of a positive correlation between building construction costs and the proportion of openings and prefabricated façade areas of external walls (Stoy et al 2008). Given the typical cost-driven decision philosophy prevailing in the industry (Wood and Ellis 2005), it is understandable that the housebuilders weighed cost criteria most heavily. Some researchers (Blismas et al 2006) have argued against this 'cost myth' and suggested developing rigorous methods for measuring the value of offsite.…”
Section: ; Gibb and Pendlebury 2005; Nao 2007)supporting
confidence: 74%
“…The criteria for selecting the successful bidder are then that bid which tend to profit maximization. Thus author proposed that bidders should submit a schedule of the payments they expect during the contract [23]. Low initial funding of the project by the contractor, delay in procurement of materials, machineries and workforces are also the major factors identified as causes of delays during the construction phase in various projects [24].…”
Section: Bidding Practices and Awardsmentioning
confidence: 99%
“…Secondly, the law allows public organizations to reject any or all the bids, the rejection cannot be done arbitrarily or in bad faith [23]. For these reasons, the decision to reject a low bid on the ground that the bidder was not responsible enough depends on the discretion of the client.…”
Section: Legal Aspectsmentioning
confidence: 99%
“…In order to achieve the predefined goals using prefabrication of house modules, a stable organizational structure throughout the whole supply chain is necessary (Wood & Ellis, 2005). The results of this study are limited to the area of specific stakeholders like architects, planners, engineers and general contractors involved in the supply chain of prefabricated housing modules.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%